Enquadres clínicos psicológicos em unidades básicas de saúde e a psicanálise proposta por Winnicott - Geraldi, Ana Vitória Borges [UNESP]; Silva, Dalila dos Santos [UNESP]; Santos, Eloisa Calemes dos [UNESP]; Silva, Gabriela Patuto [UNESP]; Amaral, Henrique Uva do [UNESP]; Vernini, Maria Eduarda de Mattos [UNESP]; Buzzo, Priscila [UNESP]; Paulillo, Thaís Souza [UNESP]; Sousa, Tatiane Patricia de [UNESP]; Ribeiro, Diana Pancini de Sá Antunes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The present work aims to promote reflections regarding the current acting of students, trainees in psychology, in the scope of public health and alsothe place of accomplishment of such acting.The students‟ activity happens through the Extention Project “Winnicottian clinical settings in Public Health” in the city of Assis – SP, registered and funded by the Export Financing Program – PROEX with the support of the Clinical Psychology Department, of the Center of Research and Applied Psychology „BettiKatzenstein‟ – CPPA, andof the Health Secretariat from the city where the project is developed. It has as its theoretical foundationthe work of Donald. W. Winnicott. Keywords: Psychoanalysis; Winnicott.

O presente trabalho tem por objetivo promover reflexões acerca da atuação dos alunos, estagiários de psicologia, no âmbito da saúde pública e também do local de realização desta atuação. A ação dos alunos se dá por meio do Projeto de Extensão “Enquadres clínicos winnicottiana na Saúde Pública” na cidade de Assis – SP, cadastrado e financiado pela Pró- reitoria de Extensão Universitária - PROEX com o apoio do Departamento de Psicologia Clínica, do Centro de Pesquisa e Psicologia Aplicada “Betti Katzenstein” – CPPA, e da Secretaria de Saúde do município sede do projeto. Possui embasamento teórico na obra de Donald W. Winnicott.
Keywords: Psychoanalysis; Winnicott; Public health; Basic health unit; Psicanálise; Winnicott; Saúde pública; Unidade básica de saúde